Public Spaces in the University: Status, Quality and Efficiency of using Student Survey at Vietnam Women's Academy - Phuong, Bui Thi; Vy, Tran Thao; Thanh Thao, Nguyen Thi; Ngoc, Duong Thi; Le, Luong Ngoc (VNU Journal of Science: Education Research; Vol 36 No 3, 2020)
The article raises some of the issues of public space for young people, especially for students, through the use of some public spaces in the school such as the school yard, hallway, canteen, library and information boards,  research about (1) how to use public space, (2) time to use it, (3) frequency of use and (4) purpose of use to evaluate the current status and effectiveness of public spaces plus (i) learning activities, (ii) entertainment, (iii) social activities and (iv) other activities. The case study of public spaces at the Vietnam Women's Academy helps researchers have an initial overview of the current situation of using public spaces in schools of students as well as assess the effectiveness , the relationship between public spaces and student activities.